Optimization of α-tocopherol and ascorbyl palmitate addition for the stabilization of sardine oil - Morales-Medina, R.; García-Moreno, P. J.; Muñío, M. M.; Guadix, A.; Guadix, E. M. (Grasas y Aceites, 2015)
The purpose of the present work was to optimize the addition of natural antioxidants (α- tocopherol and ascorbyl palmitate) for the stabilization of sardine oil rich in omega-3 PUFA. The optimal values for peroxide value (PV), which minimizes primary oxidation products, were obtained at low concentrations of α-tocopherol (50–207 ppm), high content of ascorbyl palmitate (450 ppm) and 50 ppm citric acid. On the other hand, optimal values for p-anisidine value (AV), which minimizes secondary oxidation products, were found at medium concentrations of α-tocopherol (478–493 ppm), high contents of ascorbyl palmitate (390–450 ppm) and 50 ppm citric acid. The conflicting effect of α-tocopherol on the individual optimization of PV and AV motivated the generation of a Pareto front (set of non inferior solutions) employing the weighted-sum multi-objective optimization technique.